PEMIKIRAN FAZLUR RAHMAN DALAM KAJIAN QUR’AN-HADIS (TELAAH KRITIS) - Anas Rohman (Jurnal Progress)
Abstract Fazlur Rahman is one of the new innovators in Islam that had a great influence in the 20th century, especially in Pakistan, Malaysia, Indonesia, and other countries (Islamic countries), and Chicago America (western countries) who had various thoughts related to problem. He succeeded in thinking critically both Islam and Western traditions. He succeeded in developing methods that could provide alternative solutions to contemporary Muslims. Rahman's thoughts contributed a lot to the development of Islamic studies, especially in the study of the Qur'an-Hadith. the historical-sociological approach above will create a new, dynamic, and creative discourse so that the moral ideal of the Prophet's sunnah. can be realized progressively in a variety of social phenomena and problems, so that the hadith is no longer static but becomes a living sunnah. Keywords: Thought, Fazlur Rahman, Qur'anic Hadith.